College Students’ Satisfaction on Digital-based Learning Evaluation Course in Elementary Education Program - Dina Amsari; Salmaini Safitri Syam; Fadila Suciana; Etri Wahyuni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
In today's digital era, higher education faces new challenges and opportunities, especially in terms of integrating technology in the teaching and learning process. The digital-based learning evaluation course is one form of adaptation to this change. This course is designed to equip students with skills in evaluating and managing learning that utilizes digital technology. Student satisfaction is an important indicator in assessing the effectiveness of this course. This study aims to determine student satisfaction with learning for the Digital-Based Learning Evaluation course in the Elementary School Teacher Education (PGSD) Study Program. This research was conducted using a survey method through giving a questionnaire with a total of 100 respondents who took this course. The questionnaire was given through google form with a total of 18 statements. The data were analyzed descriptively by presenting the acquisition of each aspect of satisfaction. The results show that student satisfaction is in a very high category, namely in the aspect of learning planning at 89.88%, the aspect of teaching ability of lecturers at 90.33% and the use of technology in learning at 86.37%. Thus, the learning process of the Digital-Based Learning Evaluation course has a significant effect on student satisfaction both in terms of lecturer planning and the form of technology used.